1998
DOI: 10.1139/v97-210
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylic acid pore-filled microporous membranes and their use in membrane-mediated synthesis of nanocrystalline ferrihydrite

Abstract: A series of cation-exchange membranes were obtained by photoinitiated grafting of acrylic acid onto a polypropylene microporous support having 0.2 µm diameter pores. The poly(acrylic acid) was shown to be contained within the pores of the membrane. The ion-exchange capacities of these "pore-filled" membranes ranged from 65 to 80% of the theoretical values calculated on the basis of their measured graft yields, with water contents ranging from 72 to 77%. The membranes exhibited a chemical valve effect of flux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…One method to synthesize inorganic nanoparticles employs block copolymers functionalized with carboxylic acid groups that can easily form ionic complexes with metallic compounds 16–18. Most of the copolymers and block copolymers containing carboxylic acid functionalities are based on acrylic monomers16–20 (very flexible block copolymers) and only a few studies on non‐acrylic block copolymers with carboxylic acid groups have been reported 4, 5, 21…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…One method to synthesize inorganic nanoparticles employs block copolymers functionalized with carboxylic acid groups that can easily form ionic complexes with metallic compounds 16–18. Most of the copolymers and block copolymers containing carboxylic acid functionalities are based on acrylic monomers16–20 (very flexible block copolymers) and only a few studies on non‐acrylic block copolymers with carboxylic acid groups have been reported 4, 5, 21…”
Section: Introductionmentioning
confidence: 62%
“…More recently, copolymers with functionalized N ‐substituted maleimides have been investigated as supports or templates of metallic particles,8 on the basis that inorganic nanoparticles embedded within a polymer matrix are suitable for a broad range of applications in catalysis,9, 10 magnetics11–13 and photonics 14, 15. One method to synthesize inorganic nanoparticles employs block copolymers functionalized with carboxylic acid groups that can easily form ionic complexes with metallic compounds 16–18. Most of the copolymers and block copolymers containing carboxylic acid functionalities are based on acrylic monomers16–20 (very flexible block copolymers) and only a few studies on non‐acrylic block copolymers with carboxylic acid groups have been reported 4, 5, 21…”
Section: Introductionmentioning
confidence: 99%
“…Whereas other methods use elevated temperatures for ferrihydrite/iron oxide synthesis within a porous, ion exchange membrane structure functionalized via photografting (30), here, we synthesize ferrihydrite/iron oxide nanoparticles within an easily fabricated PVDF-PAA membrane at room temperature using one of two methods. The first entails direct precipitation of the iron species within the membrane pores; the second requires the synthesis of zero-valent iron nanoparticles within the membrane pores, which then undergo deliberate oxidation to form Fe∕ Fe x O y core/shell nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…One approach to utilize the high reactivity of iron nanoparticles but overcome the aggregation and dissolution issues is to synthesize nanoparticles through ion exchange or adsorption of precursor ions on porous substrates such as silica [17], activated carbon/carbon nanotubes [18], and polyelectrolyte pore-filled membranes [1920], followed by reduction. The functional groups on those substrates can eliminate the aggregation during the particle formation and release issues to environment during the reaction, as well as allowing the control of particles size [2122].…”
Section: Introductionmentioning
confidence: 99%